Largely preserved functionality after the combined loss of NKG2D, NCR1 and CD16 demonstrates the remarkable plasticity of NK cell responsiveness - Imširović, Vanna; Lenartić, Maja; Wensveen, Felix M.; Polić, Bojan; Jelenčić, Vedrana (Frontiers in Immunology, 2023)
Natural killer (NK) cells play an important role in the early defense against tumors and virally infected cells. Their function is thought to be controlled by the balance between activating and inhibitory receptors, which often compete for the same ligands. Several activating receptors expressed on virtually all NK cells lack an inhibitory partner, most notably CD16, NCR1 and NKG2D. We therefore hypothesized that a signal through at least one of these receptors is always required for full NK cell activation. We generated animals lacking all three receptors (TKO) and analyzed their NK cells. In vitro, TKO NK cells did not show reduced ability to kill tumor targets but displayed hyperresponsiveness to NK1.1 stimulation. In vivo, TKO animals had a minor reduction in their ability to control non-hematopoietic tumors and cytomegalovirus infection, which was the result of reduced NK cell activity. Together, our findings show that activating NK cell receptors without an inhibitory partner do not provide a 'master' signal but are integrated in the cumulative balance of activating and inhibitory signals. Their activity is controlled through regulation of the responsiveness and expression of other activating receptors. Our findings may be important for future development of NK cell-based cancer immunotherapy.